PENERAPAN STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN KEMAMPUAN BERBICARA DAN MENDENGAR PADA SISWA KELAS 2 SD DI SDK JEREBUU - Gengu, Ernesta (CV Sintesia, 2024)
Speaking and listening skills are fundamental competencies that are crucial for the academic and social development of elementary school students. At the 2nd grade level, the development of these skills serves as an essential foundation for more complex communication abilities in the future. This study aims to address the challenges in developing these skills by implementing active learning strategies.This research utilizes a Classroom Action Research (CAR) approach with a cyclical design consisting of planning, implementation, observation, and reflection. The subjects of this study are 2nd grade students at SDK Jerebuu, who are divided into small groups to engage in speaking and listening activities through role-playing and group discussions. Data is collected through speaking and listening tests, student and teacher feedback questionnaires, and field notes during the learning process.The implementation of active learning strategies shows a significant improvement in students' speaking and listening skills. The average speaking test score increased from 65 to 80, and the listening test score improved from 70 to 85. Feedback questionnaires indicate that most students feel more confident speaking in front of the class and better at listening to their peers. Teacher feedback suggests that the strategy is effective in enhancing student engagement and communication skills, although challenges related to time constraints and varying student abilities were noted.Active learning strategies, including role-playing and group discussions, are effective in improving speaking and listening skills among 2nd grade students. These activities not only boost students' confidence but also facilitate better engagement in the learning process. This research suggests the use of similar strategies in other educational contexts to enhance students' communication skills.